Injonction interlocutoire - Mandamus - Immunité de la Couronne – Discrétion administrative - Paiement de subventions - Prujiner, Alain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
The function of interlocutory injunctions is changing in Quebec procedural law. Its field of operation is extending and the case of Driscoll College v. Morin opens up new perspectives as regards four points : the use of mandamus, Crown immunity, administrative discretion and the power to order the payment of a sum of money. Yet it seems that new difficulties will rise before long, which may require a complete reassessment of the interlocutory injunction's role in Quebec law.